PERBEDAAN BAHAN ATRAKTOR TERHADAP HASIL TANGKAPAN IKAN PELAGIS DENGAN MENGGUNAKAN PAYANG BUGIS DI PERAIRAN PASAURAN, PROVINSI BANTEN - Roza Yusfiandayani (Fakultas Perikanan dan Ilmu Kelautan, 2010)
Rumpon (Fish Aggregating Device) as an auxiliary gear operated in Pasauran waters, Sunda strait was longer and more widely used in Indonesia to catch pelagic fish. The characteristic species composition, size and Gonado Somato Index (GSI) pelagic fish around 3 kinds of rumpon attractor materials, i.e. Cocos nucifera, Nypa fructican and Areca catechu leaves will determine the effects of attractor materials will endanger the sustainability of pelagic fish associated. Identification and composition length, weight and GSI pelagic fish were identified in this research with different attractor material in all seasons. Experimental fishing carried out by using payang Bugis. The result show that the Cocos nucifera leaves are the best attractor material based on the number of fish species and durability in all seasons. Further, the GSI of small pelagic fish were caught around rumpon are GSI I 4 %, GSI II 33%, GSI III 35 %, GSI IV 25% and GSI V 3 %. Pelagic fish around attractor materials have GSI I-III 72%. This result indicated that the small pelagic fish caught around rumpon are â€˜immature fishâ€.